An increased fluid intake leads to feet swelling in 100-km ultra-marathoners - an observational field study - Cejka Caroline; Knechtle Beat; Knechtle Patrizia; Rüst Christoph; Rosemann Thomas (Taylor & Francis Group, 2012)
Abstract Background An association between fluid intake and changes in volumes of the upper and lower limb has been described in 100-km ultra-marathoners. The purpose of the present study was (i) to investigate the association between fluid intake and a potential development of peripheral oedemas leading to an increase of the feet volume in 100-km ultra-marathoners and (ii) to evaluate a possible association between the changes in plasma sodium concentration ([Na+]) and changes in feet volume. Methods In seventy-six 100-km ultra-marathoners, body mass, plasma [Na+], haematocrit and urine specific gravity were determined pre- and post-race. Fluid intake and the changes of volume of the feet were measured where the changes of volume of the feet were estimated using plethysmography. Results Body mass decreased by 1.8 kg (2.4%) (p < 0.0001); plasma [Na+] increased by 1.2% (p < 0.0001). Haematocrit decreased (p = 0.0005). The volume of the feet remained unchanged (p > 0.05). Plasma volume and urine specific gravity increased (p < 0.0001). Fluid intake was positively related to the change in the volume of the feet (r = 0.54, p < 0.0001) and negatively to post-race plasma [Na+] (r = -0.28, p = 0.0142). Running speed was negatively related to both fluid intake (r = -0.33, p = 0.0036) and the change in feet volume (r = -0.23, p = 0.0236). The change in the volume of the feet was negatively related to the change in plasma [Na+] (r = -0.26, p = 0.0227). The change in body mass was negatively related to both post-race plasma [Na+] (r = -0.28, p = 0.0129) and running speed (r = -0.34, p = 0.0028). Conclusions An increase in feet volume after a 100-km ultra-marathon was due to an increased fluid intake.